Doutoramento Honoris Causa Sua Alteza o Xeque Doutor Sultan bin Muhammad bin Saqr bin Khalid bin Sultan bin Saqr bin Rashid - Muhammad bin Saqr bin Khalid bin Sultan bin Saqr bin Rashid Al Qasimi (Outros Títulos, 2019)
This volume gathers the texts of the speeches given at the doctorate honoris causa in Arts and Humanities awarded by the University of Coimbra to His Highness the Sheikh Dr. Sultan bin Muhammad bin Saqr bin Khalid bin Sultan bin Saqr bin Rashid Al Qasimi, in which Dr. Margarida Neto was presenter.